Application of 5G technology to conduct tele‐surgical robot‐assisted laparoscopic radical cystectomy. Issue 4 (4th May 2022) - Yang, Xuecheng; Wang, Yonghua; Jiao, Wei; Li, Jianmin; Wang, Bingqiang; He, Long; Chen, Yongjian; Xuesong Gao,; Li, Zhaoyu; Zhang, Yu; Li, Huanting; Wang, Chen; et al.
Abstract: Background: The aim of this study was to test the effectiveness, safety and stability of the 5G communication technology in clinical laparoscopic telesurgery. Methods: An ultra‐remote radical cystectomy (network communication distance of nearly 3000 km) was performed on patient diagnosed with T2N0M0 stage bladder cancer using a domestically produced "MicroHand" surgical robot. Results: The network delay, operative time, blood loss, intraoperative complications, postoperative recovery, and hospitalisation time were recorded. The 5G network was used throughout the operation, with an average total delay of 254 ms. The operation went well and the patient recovered smoothly. Conclusions: Ultra‐remote clinical laparoscopic surgery can be performed safely and smoothly. More importantly, our model can provide insights for promoting the future development of telesurgery in China.